2022
DOI: 10.1088/1361-6463/ac89fc
|View full text |Cite
|
Sign up to set email alerts
|

DC and low-frequency noise characteristics of GaN-based HEMTs under cryogenic temperatures

Abstract: In this work, the device characteristics of GaN-based high-electron-mobility transistors (HEMTs) were systematically investigated by the direct current (DC) and low-frequency noise (LFN) measurements within the temperature ranging from 300 K to 4.2 K. The temperature-dependent behavior of the on- and off-state electrical properties was statistically analyzed, highlighting an overall improved device performance under the cryogenic temperatures. In addition, the LFN of the device exhibited an evident behavior of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Comparison curves of the mobility model (solid lines) with experimental data (symbols) at different temperature ranges: a) low temperatures [ 41,45 ] and b) high temperatures. [ 46 ] …”
Section: Model Descriptionmentioning
confidence: 99%
See 3 more Smart Citations
“…Comparison curves of the mobility model (solid lines) with experimental data (symbols) at different temperature ranges: a) low temperatures [ 41,45 ] and b) high temperatures. [ 46 ] …”
Section: Model Descriptionmentioning
confidence: 99%
“…The fitting results of the I – V model and the measured data of GaN HEMT on the GaN‐on‐sapphire template in ref. [45] are shown in Figure . Figure 5a shows the transfer characteristic curves in linear and semi‐logarithmic coordinates over the temperature range of 4.2–300 K (−268.8–27 °C), and it can be found that as the temperature changes from 300 to 4.2 K, the electrical performance of the device improves significantly, with a significant increase in saturation current and a steeper sub‐threshold swing.…”
Section: Model Verification and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…* Author to whom any correspondence should be addressed. two-dimensional electron gases (2DEGs) at the AlGaN/GaN hetero-interface [4][5][6]. As a result, such devices have emerged as competitive candidates in various applications such as electric vehicles, wireless communication, data centre, etc [7].…”
Section: Introductionmentioning
confidence: 99%